Sociological calculation as a instrument in politics and environmental economy - Ciszek, Mariusz; Świderski, Andrzej W. (Studia Ecologiae et Bioethicae, 2005)
This study show indicate idea of eco-development on environmental economy. Particularly marked interaction of connection between ecological losses and sociological calculation. Layout for this study is as follow: eco-development as goal for politics and environmental economy, ecological losses in microeconomic and macroeconomic, evaluation in ecological harms in sociological calculation.